Anti-melanoma differentiation-associated gene 5 antibody-positive dermatomyositis complicated with macrophage activation syndrome - Yukang Ding (Therapeutic Advances in Chronic Disease, 2022)
Background: Anti-melanoma differentiation-associated gene 5 (anti-MDA5) antibody-positive dermatomyositis (DM) has low survival rate, whereas macrophage activation syndrome (MAS) is a severe and life-threatening syndrome associated with autoimmune diseases. Their coexistence is very rare. This study aimed to describe the prevalence, clinical characteristics, and outcomes of anti-MDA5 antibodies-positive DM patients complicated with MAS. Methods: In this retrospective study, we enrolled DM patients with anti-MDA5 antibodies, who were hospitalized between 2016 and 2020 and included patients diagnosed with MAS. Results: We identified four (2%) DM patients with anti-MDA5 antibodies. They were females with interstitial lung disease (ILD). The level of aspartate aminotransferase (AST), lactate dehydrogenase (LDH), and ferritin were significantly higher in the MAS group than those without MAS ( p  < 0.05). Patients with MAS were significantly more likely to develop a dysphagia ( p  = 0.012). Literature review revealed eight similar cases. Together with the present study, we identified 12 patients complicated with ILD. The median age of disease onset was 52 years with a male to female ratio of 1:6. The median duration between DM onset and MAS diagnosis was 3 months. The mortality of MAS in anti-MDA5 antibody-positive DM was 50%. Patients who died were older than those who survived (56.7 years versus 35.5 years; p  = 0.015). Conclusions: MAS was rare in anti-MDA5 antibody-positive DM. The higher the level of AST, LDH, and ferritin, the greater the risk of MAS. They were associated with high mortality rates, particularly in older patients.